Potensi Biomassa Dan Karbon Tersimpan Tegakan di Ruang Terbuka Hijau Kota Polewali, Sulawesi Barat - Daud Irundu; Mir A Beddu; Najmawati Najmawati (Jurnal Hutan dan Masyarakat, 2020)
Global warming is one of the major environmental issues of this century. Carbon dioxide (CO2) emissions are the main cause of global warming. Green open space (RTH) such as urban parks, urban forests and green lines play an important role in mitigating global warming and climate change in urban areas because it is able to reduce CO2 from the atmosphere. This study aims to determine the potential of biomass and carbon stored in the Green Open Green Space of Polewali, West Sulawesi. Data collection for stored biomass and carbon is carried out at three green space locations including; Urban forest and city park and green lane each made three plots measuring 20 m x 20 m, and three plots on the Green Line measuring 1200 m. Retrieval of data by measuring tree height and diameter, analysis to obtain the dry volume, biomass and carbon stored for each tree species contained in the Polewali green space. Biomass is obtained by the formula M = BJ x Vk x BEF, the stored carbon value is obtained from the product of biomass by 0.47. The magnitude of the relationship of volume with biomass and carbon uses a regression equation (Ŷ=a+bX). The results show there are types of Glodokan (Polyalthia longifolia), Johar (Senna siamea), Mahogany (Swetenia sp) and Trambesi (Samanea saman) which are spread in the Polewali open green space. Trambesi is a type that has dominant biomass and stored carbon of 381.95 (tons / ha) and 179.52 (ton/ha). Green lane is the type of green space that has the most stored carbon and is currently 440.94 (ton/ha) and 207.24 (ton/ha). The overall green space biomass is 571.83 (ton/ha) and stored carbon is 268.76 (ton/ha) found in urban forests, urban gardens and green belt. The relationship of volume with biomass and stored carbon shows a very strong relationship with the coefficient of determination (R2) of 0.96.